Tuneable magnetic moments in superatomic CuXNi8−X clusters. (21st August 2019) - Gilmour, J T A; Gaston, N
Abstract: The geometries and electronic structures for Cu X Ni8− X ( X = 1–8) clusters have been elucidated using density functional theory methods. These clusters have been demonstrated to be eight superatomic electron species, with a substantial HOMO-LUMO gap and closed 1 S and 1 P subshells. Through sequential replacement of copper atoms for nickel in these clusters it has been shown that the magnetic moment of bimetallic clusters can be controllably altered, with the nickel atoms localising spin density in their 3 d orbitals.